Mesenchymal stem cells in craniofacial reconstruction: a comprehensive review - Zheng, Zizhuo; Liu, Hanghang; Liu, Shibo; Luo, En; Liu, Xian (Frontiers in Molecular Biosciences, 2024)
Craniofacial reconstruction faces many challenges, including high complexity, strong specificity, severe injury, irregular and complex wounds, and high risk of bleeding. Traditionally, the "gold standard" for treating craniofacial bone defects has been tissue transplantation, which involves the transplantation of bone, cartilage, skin, and other tissues from other parts of the body. However, the shape of craniofacial bone and cartilage structures varies greatly and is distinctly different from ordinary long bones. Craniofacial bones originate from the neural crest, while long bones originate from the mesoderm. These factors contribute to the poor effectiveness of tissue transplantation in repairing craniofacial defects. Autologous mesenchymal stem cell transplantation exhibits excellent pluripotency, low immunogenicity, and minimally invasive properties, and is considered a potential alternative to tissue transplantation for treating craniofacial defects. Researchers have found that both craniofacial-specific mesenchymal stem cells and mesenchymal stem cells from other parts of the body have significant effects on the restoration and reconstruction of craniofacial bones, cartilage, wounds, and adipose tissue. In addition, the continuous development and application of tissue engineering technology provide new ideas for craniofacial repair. With the continuous exploration of mesenchymal stem cells by researchers and the continuous development of tissue engineering technology, the use of autologous mesenchymal stem cell transplantation for craniofacial reconstruction has gradually been accepted and promoted. This article will review the applications of various types of mesenchymal stem cells and related tissue engineering in craniofacial repair and reconstruction.